The importance and factors of enjoyment In Malaysian ESL classroom: A multisite case study - Norfadzillah Chin; Noraini Said; Chelster Sherralyn Jeoffrey Pudin; Wardatul Akmam Din (Global Academic Excellence, 2022)
Affective factors such as emotion and attitudes have long been identified as contributing factors to success and enjoyment in language learning. With the new movement of education in the new norm, a weightage needs to be focused on the affective dimensions among learners. This study aimed to discover the importance and factors of enjoyment in learning English as a Second Language (ESL) among Malaysian secondary school students. This multisite case study took place in five secondary schools in Malaysia. Focus Group Discussion (FGD) was held among five ESL teachers and an open-ended questionnaire was distributed to 65 students in the respective schools. The findings reveal both teachers and students think enjoyment is important in learning ESL as it bridges up engagement in learning, enhances motivation and for the usefulness of learning the language. Furthermore, the study also discovers the factors of enjoyment in learning ESL namely teacher-factor, sense of achievement and relationship with peers. This study provides valuable information on the of the understudy topic of enjoyment in Malaysian ESL classroom.